Study of gas hydrate metastability and its decay for hydrate samples containing unreacted supercooled liquid water below the ice melting point using pulse NMR. (1st December 2015) - Madygulov, Marat Sh.; Nesterov, Anatoliy N.; Reshetnikov, Alexey M.; Vlasov, Valeriy A.; Zavodovsky, Alexey G.
Abstract: The behavior of bulk Freon-12 hydrate samples containing inclusions of unreacted liquid water below the ice melting point at pressures below the hydrate–ice–gas equilibrium pressure has been studied using nuclear magnetic resonance (NMR) spectroscopy. The amount of liquid water in the samples was directly measured by transverse relaxation measurements of the hydrogen nucleus of the system studied. An evidence of the long-lived existence of gas hydrate as a metastable phase and hydrate dissociation into supercooled water and gas has been presented. It was shown that the dissociation of the bulk metastable hydrate into supercooled water and gas was reversible. An influence of the phase state of the unreacted water in the samples on the stability of the metastable hydrate and mechanism of hydrate dissociation was revealed: ice crystallization led to the decay of the hydrate metastability and the hydrate dissociation into ice and gas. Graphical abstract: Highlights: Behavior of metastable bulk gas hydrate samples below 273 K was studied by 1 H NMR. Metastable hydrate can contain residual supercooled water but does not contain ice. Dissociation of metastable hydrate into supercooled water and gas is reversible. Ice crystallization leads to the decay of the hydrate metastability.